Out in Morocco: homosexuality and transnationalism in the writings of Rachid O. and Abdellah Taïa - Panizzon, P (2020)
This is the first comprehensive study of the work of Rachid O. and Abdellah Taïa, two contemporary Moroccan authors whose writings deal with same-sex desire. Offering a close reading of the work of Rachid O. and Taïa, this study assesses how same-sex desire is expressed in a discursive space which does not acknowledge homosexuality and to what extent these forms of desire need to be situated in the transnational space and amid the sexual-political context of Morocco and the West. One of the foci of this study is to compare and contrast queer contemporary Moroccan writing with western queer theory and to examine to what extent Rachid O.’s and Taïa’s writings challenge or inform queer western scholarship. I offer two principal arguments. First, I suggest that Rachid O. and Abdellah Taïa loosen rigid ideologies around masculinity, sexuality, and gender in Arab/Muslim culture and offer a new understanding of sexuality and sexual orientation in their culture. By re-appropriating a heritage around same-sex love rooted in Arab/Muslim culture, they proffer a more inclusive, visionary idea of Islam, affording space for the sexually different. Second, I demonstrate that the invention of different ways of experiencing masculinity, homosexuality, and Islam is also facilitated by the West – specifically France. It illustrates how both authors critically engage with western modes of homosexuality, the notion of being ‘out’, the idea of living in an equal relationship with a same-sex partner, sometimes adopting these models, sometimes creating hybrid forms, often, however, problematically distancing themselves from western concepts and assessing their racial bias. Drawing upon western queer theory, postcolonial studies and a wide range of sociological accounts of homoeroticism in the West and North African society, this study makes an empirical and theoretical contribution to queer theory, to transnational conceptualizations of gender and sexuality, and to new understandings of masculinity in Morocco today.